Why is there a lack of girls in STEM careers and what can schools do about it? - Wright, Emily (2017)
Despite the increased understanding of the importance of science, technology, engineering and maths (STEM), it is still a male dominated career with only 13% of the overall workforce being female. There is a lot of research into different ways to engage more girls in STEM, however not much from the perspectives of students or how different causal factors link together to cause this gender divide. To investigate the reasons for a lack of girls in STEM in my educational context and what I can do about it, I held focus groups with girls studying STEM A Levels and separately girls who did not. I developed their ideas further by holding a focus group with teaching staff in STEM departments to get their opinion and finally contacted multiple Women in STEM organisations to validate the statements the girls made. In comparison to the control group, the girls on the STEM pathway had more parental support, higher attainment, higher confidence and enjoyed STEM subjects a lot more. The findings, validated by the teacher focus group and the ‘Women in STEM’ groups, support the theory that multiple causal factors require a multistep process. The following statements summarise the findings: Target careers advice to all students and make STEM lessons more enjoyable and practical, improve students’ passion and attainment, improve the amount of praise from parents and teachers, improve students’ confidence, thus students are more likely to pursue a STEM career. These factors working together could in theory improve the number of girls choosing STEM A Levels and beyond.